Preparation of Ethylene Scavenger Based on KMNO4 to the Extension of the Storage Time of Tomatoes - Dobrucka, Renata; Leonowicz, Andrzej; Cierpiszewski, Ryszard (Studia Oeconomica Posnaniensia, 2017)
Ethylene is one of the simplest plant growth regulators and is known to play a role in many physiological processes in fruit and vegetables. It helps to accelerate ripening in fruit, followed by aging and ultimately death. It is known that much fresh produce emits relatively large amounts of ethylene and smaller amounts of alcohol, aldehyde, and ester vapours in addition to carbon dioxide. The effect on the respiration rate depends primarily on the relative concentration compared to the ethylene emission of the plant, rather than on the absolute ethylene concentration. The removal of ethylene gas from the package headspace slows senescence and prolongs shelf life. Various methods of ethylene control are offered commercially, including several based on ethylene adsorption/oxidation. The aim of this study was to prepare an ethylene scavenger with the use of potassium permanganate. The prepared ethylene scavenger was used extend the storage time of fresh tomatoes. The storage conditions were similar to tomato vegetable storage conditions at home and on shop shelves. This test used three equal groups (five replicates per group) and placed them in commercial plastic packaging. The first group of tomatoes was placed in packaging without any ethylene absorber, while the other two groups were placed in packaging with any ethylene absorber. The sachets placed in the packaging contained respectively 1 and 2 grams of previously prepared ethylene absorber. The first mold on the tomatoes in the packaging with ethylene absorber occurred on the ninth day of the experiment. In the two remaining packets, mold appeared after nearly fifty days. There were differences in the first group of stored tomatoes. Also, the obtained results confirmed the possibility of using ethylene absorber with zeolite for food storage.